2013
DOI: 10.1590/s0100-06832013000300025
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon and nitrogen stocks in traditional agricultural and agroforestry systems in the semiarid region of Brazil

Abstract: SUMMARYIn the semiarid region of Brazil, inadequate management of cropping systems and low plant biomass production can contribute to reduce soil carbon (C) and nitrogen (N) stocks; therefore, management systems that preserve C and N must be adopted. This study aimed to evaluate the changes in soil C and N stocks that were promoted by agroforestry (agrosilvopastoral and silvopastoral) and traditional agricultural systems (slash-and-burn clearing and cultivation for two and three years) and to compare these sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
(43 reference statements)
0
17
0
10
Order By: Relevance
“…It seems that this is a common pattern observed for different crops and different types of land management in several regions of Brazil, like in the northeast (Lima et al, 2011;Fracetto et al, 2012;Barros et al, 2013;Sacramento et al, 2013), in central Brazil (Cardoso et al, 2010;Silva et al, 2011;Guareschi et al, 2012) and in the south (Sisti et al, 2004;Sá et al, 2013;Santana et al, Figure 5. Scatter plot of soil carbon stock losses (data from Assad et al, 2013), and soil nitrogen stock losses found in our study between pasture and native vegetation in the paired study sites (a) 0-10 cm, (b) 0-30 cm and (c) 0-60 cm depth intervals.…”
Section: Land-use Changes Alter Nitrogen and Phosphorus Stocksmentioning
confidence: 74%
See 1 more Smart Citation
“…It seems that this is a common pattern observed for different crops and different types of land management in several regions of Brazil, like in the northeast (Lima et al, 2011;Fracetto et al, 2012;Barros et al, 2013;Sacramento et al, 2013), in central Brazil (Cardoso et al, 2010;Silva et al, 2011;Guareschi et al, 2012) and in the south (Sisti et al, 2004;Sá et al, 2013;Santana et al, Figure 5. Scatter plot of soil carbon stock losses (data from Assad et al, 2013), and soil nitrogen stock losses found in our study between pasture and native vegetation in the paired study sites (a) 0-10 cm, (b) 0-30 cm and (c) 0-60 cm depth intervals.…”
Section: Land-use Changes Alter Nitrogen and Phosphorus Stocksmentioning
confidence: 74%
“…On the other hand, there are few regional studies considering how nitrogen and phosphorus soil contents will be affected in these integrated agricultural systems. Plot-level studies have reported a decrease in soil nitrogen stocks with cultivation in several N-fertilized areas of Brazil and under different cropping systems (Lima et al, 2011;Fracetto et al, 2012;Barros et al, 2013;Sacramento et al, 2013;Cardoso et al, 2010;Silva et al, 2011;Guareschi et al, 2012;Sisti et al, 2004;Santana et al, 2013;Sá et al, 2013). The same trend has been observed in Chernozem soils in Russia and in prairie soils of Wisconsin in the USA (Mikhailova et al, 2000;Kucharik et al, 2001).…”
mentioning
confidence: 99%
“…In most of the plot-level paired sites and in most of the regional soil survey, we found a loss of nitrogen compared to the native vegetation. It seems that this is a common pattern observed for different crops and different types of land management in several regions of Brazil, like in the northeast (Lima et al, 2011;Fracetto et al, 2012;Barros et al, 2013;Sacramento et al, 2013), in central Brazil (Cardoso et al, 2010;Silva et al, 2011;Guareschi et al, 2012) and in the south (Sisti et al, 2004;Sá et al, 2013;Santana et al, Figure 5. Scatter plot of soil carbon stock losses (data from Assad et al, 2013), and soil nitrogen stock losses found in our study between pasture and native vegetation in the paired study sites (a) 0-10 cm, (b) 0-30 cm and (c) 0-60 cm depth intervals.…”
Section: Land-use Changes Alter Nitrogen and Phosphorus Stocksmentioning
confidence: 74%
“…On the other hand, the conventional cassava system had 54% less carbon than the secondary forest. Sacramento et al (2013), comparing conservationist systems against conventional systems, verified that the forest-crop-livestock system caused less loss of C, compared to the conventional system, where losses were up to 58.87 Mg ha -1 .…”
Section: ----------------------------G Kg -1 ------------------------mentioning
confidence: 93%